Aptamer‐aptamer linkage based aptasensor for highly enhanced detection of small molecules. Issue 6 (25th May 2016) - Nguyen, Van‐Thuan; Lee, Bang Hyun; Kim, Sang Hoon; Gu, Man Bock
Abstract: The multi‐target colorimetric aptasensors can be easily fabricated by using two different aptamer sequences. However, there have been no research reports about improvement or enhancing of colorimetric signals based on the aggregation properties of AuNPs. Herein, we report a simple and efficient method to control and enhance the function of the multi‐target aptasensor using an aptamer‐aptamer linkage method. The aptasensor was developed for highly sensitive multiple‐target detection of small molecules. The extension of aptamer DNA sequences using this method resulted in the enhanced analytical sensitivity of this aptasensor in sensing applications for two small molecule targets. Furthermore, the mechanism of the interaction between DNA aptamer and AuNPs was studied by measuring the zeta potential to explain the enhancement of the sensitivity of this multi‐target aptasensor. The limit of detection of this multi‐target aptasensor was found to be 1 nM and 37 nM for kanamycin (KAN) and chlortetracycline (CHLOR), respectively. It is 25‐fold lower than in the previous report using an AuNP‐based sensor for defining the limit of detection (LOD) of KAN and five times lower than the LOD for CHLOR. This aptasensor has great potential in the simultaneous detection of a wide range of KAN and CHLOR concentrations. Abstract : Two different aptamers are successfully combined in order to detect two antibiotics, kanamycin and chlortetracycline, which should be monitored quickly and sensitively in food and environment. In addition, the authors explain how DNA aptamer and gold nanoparticles interact with each other to increase the sensitivity of this colorimetric aptasensor. By using this biosensor, they can detect kanamycin up to 1nM and chlortetracycline 37nM, which has been greatly improved than previous reports. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB, visitwww.afob.org .